Oocytectomy does not influence synthesis of hyaluronic acid by pig cumulus cells: retention of hyaluronic acid after insulin-like growth factor-I treatment in serum-free medium - Nagyová, E; Procházka, R; Vanderhyden, B C (Biology of reproduction, 1999)
Mouse oocytes secrete a factor that enables cumulus cells to undergo expansion in response to FSH (1 microg/ml), whereas expansion of the porcine cumulus oophorus has been shown to be independent of the oocyte. The aim of this study was to assess FSH-induced synthesis of hyaluronic acid (HA) by porcine cumulus cells before and after oocytectomy. In addition, we studied the effect of insulin-like growth factor-I (IGF-I) on the ability of cumulus cells to synthesize and retain HA in response to FSH in serum-free medium. Porcine oocyte-cumulus complexes and complexes from which the oocytes had been removed by oocytectomy were cultured for 24 h in the presence of 2.5 microCi of D-[6-(3)H]glucosamine hydrochloride, fetal calf serum (FCS, 5%), and FSH. After 24 h, incorporation of [(3)H]glucosamine into HA was measured either in complexes alone (retained HA) or in medium plus complexes (total HA). Specificity of incorporation of radioactivity into HA was confirmed by the sensitivity to highly specific Streptomyces hyaluronidase. Our results suggest that 1) the synthesis of HA by pig cumulus cells in vitro is stimulated by FSH and that oocytectomy does not change this synthesis; 2) oocytes do not influence retention of HA within the complex; 3) FSH-induced synthesis of HA by cumulus cells is decreased in medium with polyvinylpyrrolidone (PVP)-supplemented (total and retained HA) compared to FCS-supplemented medium; 4) IGF-I enabled cumulus cells to synthesize HA in response to FSH in PVP-supplemented medium in a manner similar to that observed when serum is present in the medium.
Keywords: Culture Media, Serum-Free; Insulin-Like Growth Factor I; Female; Follicle Stimulating Hormone; folikuly stimulující hormon; insulinu podobný růstový faktor I; Cells, Cultured; zvířata; oocyty; Swine; ženské pohlaví; kultivované buňky; kyselina hyaluronová; ovariální folikul; kultivační média bez séra; Ovarian Follicle; Animals; Hyaluronic Acid; Oocytes; prasata